Why don't people pay attention? Endogenous Sticky Information in a DSGE Model - Lena Dräger (Hamburg University, Department Economics and Politics, 2010)
Building on the models of sticky information, we endogenize the probability of obtaining new information by introducing a switching mechanism allowing agents to choose between costly rational expectations and costless expectations under sticky information. Thereby, the share of agents with rational expectations becomes endogenous and time-varying. While central results of sticky information models are retained, we find that the share of rational expectations is positively correlated with the variance of the variable forecasted, providing a link to models of near-rationality. Output expectations in our model are generally more rational than inflation expectations, but the share of rational inflation expectations increases with a rising variance of the interest rate. With regard to optimal monetary policy, we find that the Taylor principle provides a necessary and sufficient condition for determinacy of the model. However, output and inflation stability are optimized if the central bank does not react too strongly to inflation, but rather also targets the output gap with a relatively large coefficient in the Taylor rule.
Keywords: E31; E52; E61; 330; Endogenous sticky information; heterogeneous expectations; DSGE models